The tale of Cho Ung : a classic of vengeance, loyalty, and romance - Cho, Sookja (Translations from the Asian classics., 2018)
The Tale of Cho Ung is one of the most widely read and beloved stories of Chosŏn Korea. The anonymously written tale recounts the adventures of protagonist Cho Ung as he fearlessly confronts and overcomes obstacles and grows into a heroic young man. As a child, Ung flees a wicked tyrant who wrongfully killed his father and took advantage of the emperor's death to seize the throne from the young prince. Driven by his passion, righteousness, and sense of duty, he pursues retribution and restores justice. His journey, from its innocent beginnings to his final triumph, unfolds as a complex tapestry of loyalty, honor, retribution, and love interspersed with threads of romance and the supernatural.This first translation into English of The Tale of Cho Ung offers a glimpse into the vernacular and popular literature of the late Chosŏn period, exemplifying the types of stories and heroes that were favored by its reading public. The tale emphasizes individual affections and ethics between child and parent, husband and wife, subject and ruler, pupil and teacher, yet explores human life in all its complexity, even subtly dissenting against traditional Korean social norms. This unabridged translation draws upon the many surviving editions of the novel, which vary in length and format. In her introduction, Sookja Cho addresses how the novel evolved and changed over time, while her annotations help to reveal the depths of a text that conveys the richness and complexity of premodern Korean literature and culture.